Zjawisko lęku językowego w procesie nauki języka niemieckiego - Bawej, Izabela (Neofilolog, 2017)
The article discusses the problem of language anxiety in foreign language learning. The author presents definitions and typologies anxiety, the biological symptoms of anxiety and their interpretation. A research study, conducted on a group of students of Applied Linguistics is described. The investigation included if they are afraid of speaking in German classes and during the exam, or if they are afraid of their German teacher. The results of the study show that communication apprehension, test anxiety, social anxiety, final grades, attitude to the teacher, and self-assessment are some of the reasons for language anxiety in the foreign language learning process.